1972
DOI: 10.1021/i360043a005
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulations of Transport Processes

Abstract: He received the BS degree from the University of Michigan and the MS and PhD degrees from Massachusetts Institute of Technology. Before joining the University of Pittsburgh, he was associated vrith A bear Inc., Cambridge, MA. During the year 1970-71, he was a visiting scholar at the University of Cambridge, Cambridge, U.K, He presently teaches courses in reaction engineering and has research interests in reaction engineering and special types of transport phenomena.Recent developments in computer technology ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Shah et al indeed reported that 25−35% of clinical trial patients treated with TKI showed a low-grade elevation in alanine and/or aspartate aminotransferases, and approximately 2% of them developed high-grade increases in serum transaminases, with a wide variability among TKI. 8 Although little is known about the underlying mechanisms, it is thought that liver toxicity could be due to reactive metabolites (RM) and as well as being immune-related. RM reactivity is associated with the presence of electrophilic moieties or radicals originating from the metabolic transformation, often called bioactivation, of particular functional groups known as structural alerts or toxicophores.…”
Section: Introductionmentioning
confidence: 99%
“…Shah et al indeed reported that 25−35% of clinical trial patients treated with TKI showed a low-grade elevation in alanine and/or aspartate aminotransferases, and approximately 2% of them developed high-grade increases in serum transaminases, with a wide variability among TKI. 8 Although little is known about the underlying mechanisms, it is thought that liver toxicity could be due to reactive metabolites (RM) and as well as being immune-related. RM reactivity is associated with the presence of electrophilic moieties or radicals originating from the metabolic transformation, often called bioactivation, of particular functional groups known as structural alerts or toxicophores.…”
Section: Introductionmentioning
confidence: 99%